(untitled) (Forum Penelitian Agro Ekonomi, 2024)
Since Indonesia’s independence up to the reform era, land reform is acknowledged but it has not been effectively implemented. However, there is also an inverse process called as de-land-reform with its objectives inconsistently with the ideal purposes of land reform. It seems as the natural symptoms due to social-economic political environment and inside condition of the farmers themselves. De-land-reform process gets no attention, so far, and no serious efforts to cope with it. De-land-reform consists of selling farmers’ land, land fragmentation such that it does not achieve scale of economy, and uncontrollable land conversion. This is due to social-economic political pressures, and community’s social-culture. It needs common awareness as an initial phase of control, but, unfortunately, the government, community, and observers do not pay attention to this process.